High-3He/4He, depleted mantle and low-δ18O, recycled oceanic lithosphere in the source of central Iceland magmatism. - Macpherson, C. G.; Hilton, D. R; Day, J. M. D; Lowry, D.; Gronvold, K. (Earth and Planetary Science Letters, 2005)
New helium and oxygen isotope data and trace element concentrations are reported for volcanic rocks from central Iceland. Basalts that are depleted in the most incompatible trace elements possess a wide range in 3He/4He but most ratios are similar to or higher than those of mid-ocean ridge basalt (MORB:~8RA[1] [D.W. Graham, Noble gas geochemistry of mid-ocean ridge and ocean island basalts: characterisation of mantle source reservoirs, in: D.P. Porcelli, C.J. Ballentine, R. Wieler (Eds.), Noble gases in Geochemistry and Cosmochemistry, Rev. Mineral. Geochem., vol. 47, 2002, pp. 247–317]). The low concentrations of helium in these rocks suggest that significant degassing has made them susceptible to contamination by low-3He/4He crust, therefore all measured 3He/4He are considered minimum estimates for their sources. Elevated helium isotope ratios in the source of these rocks result from interaction with high-3He/4He mantle. The highest oxygen isotope ratios in the depleted rocks are similar to those in melts from typical depleted upper mantle and the range of d18O values is consistent with variable, limited amounts of contamination by Icelandic crust. Most of the incompatible trace element-enriched rocks possess 3He/4He ratios that are similar to or lower than those in MORB. These rocks were erupted close to the postulated centre of the Iceland plume. This observation contradicts models in which high-3He/4He characterises the focus of mantle upwelling. A source with MORB-like 3He/4He ratios may also be common to other parts of the North Atlantic Igneous Province. The highest d18O values in the enriched rocks are lower than those in MORB and do not appear to have been affected by interaction with low-d18O Icelandic crust. Recycling of hydrothermally altered oceanic crust that has been subducted into the mantle provides a plausible mechanism for generating an 18O-poor source with the trace element and isotopic characteristics of the enriched lavas.